Natural Occurrence of Toxigenic Fusarium proliferatum on Paddy (Oryza sativa L.) in Karnataka, India - Pavagada Krishnamurthy Maheshwar; Gottravalli Ramanayaka Janardhana (Tropical Life Sciences Research, 2010)
Contamination of paddy seeds (rice with husk) by Fusarium species can cause spoilage and subsequent production of mycotoxins, especially fumonisins that affect human and animal health. A mycological study was conducted to evaluate the natural occurrence of fumonisin B1 produced by Fusarium proliferatum on paddy grown in different geographic regions of Karnataka (India). A total of 65 isolates of F. proliferatum from paddy samples were analysed by polymerase chain reaction (PCR). One set of primers, Fp3-F and Fp4-R was employed to identify the species F. proliferatum, and another set of primers, FUM1 was employed to determine the fumonisin producing ability of the isolates. All 65 isolates of F. proliferatum scored positive with both set of primers, producing amplified products of the expected sizes. Furthermore, thin layer chromatography (TLC) analysis detected fumonisin B1 (FB1) in all of the PCR positive isolates of F. proliferatum. Pencemaran biji benih padi (beras bersama sekam/ sekam padi) oleh spesies Fusarium boleh mengakibatkan kerosakan dan diikuti dengan penghasilan mikotoksin, terutamanya fumonisin yang memberi kesan terhadap kesihatan manusia dan haiwan. Satu kajian mikologi telah dijalankan untuk menilai penghasilan fumonisin secara semulajadi oleh Fusarium proliferatum dalam padi yang tumbuh di kawasan-kawasan geografi berbeza di Karnataka (India). Sejumlah 65 sampel F. proliferatum diasingkan daripada padi dan dianalisa menggunakan polymerase chain reaction (PCR). Satu set primer-primer Fp3-F dan Fp4-R telah digunakan untuk mengenal pasti spesies F. proliferatum manakala satu lagi set primer-primer, FUM1 telah digunakan untuk mengenal pasti kebolehan menghasilkan fumonisin. Kesemua 65 sampel F. proliferatum memberi keputusan positif kepada kedua-dua set primer, dengan menghasilkan produk yang dibesarkan kepada saiz yang dijangka. Tambahan lagi, melalui analisa thin layer chromatography (TLC), fumonisin B1 (FB1) telah dikesan di kesemua sampel F. proliferatum yang memberi keputusan PCR yang positif.